The role of definitive local treatment in metastatic hepatocellular carcinoma patients: A SEER-based study. Issue 10 (March 2018) - Su, Mingxue; Zhao, Yuanyuan; Liu, Jianjun
Abstract : Abstract: In the present study, we aimed to investigate the survival benefit from definitive local treatment (LT) for hepatocellular carcinoma patients with distant metastasis (mHCC). We retrospectively analyzed mHCC patients from Surveillance, Epidemiology, and End Results (SEER) Database. The patients' clinical and pathological characteristics were analyzed. Overall survival (OS) was calculated by Kaplan-Meier method. Independent risk factors associated with disease special mortality (DSM) were identified by multivariable regression analysis. A total of 7187 mHCC patients from SEER database were identified. A total of 258 (3.6%) patients had received surgery treatment (ST), 64 (0.9%) patients underwent radiotherapy (RT), and 6865 (95.5%) patients were identified to no surgery or radiation therapy group (NSR). Compared with the patients in NSR group, patients who received ST (hazard ratio [HR]: 0.26, 95% confidence interval [CI] 0.22–0.31, P < .001) and RT (HR: 0.51, 95% CI 0.38–0.67, P < .001) had decreased DSM. Patients with age >50 years, female, and T3 or higher stage were associated with increased DSM. The present study demonstrated the survival benefit of definitive LT in mHCC patients. However, a large randomized clinical trial to validate the role of LT in mHCC is necessary in the future. Abstract : Supplemental Digital Content is available in the text